CASA DE PASSARINHO: A experiência com a infância vivenciada pelas crianças em uma instituição de acolhimento em Imperatriz - MA. - LIMA, Jéssica de Sousa (2021)
Based on the assumption that there is no rigid and universal concept of childhood, but that children have different experiences with this phase of the life cycle, depending on the circumstances in which they find themselves, this work focuses on the analysis of how childhood it is experienced by children who reside in a shelter. When we reflect on these children who were removed from their families - responsible for putting them in situations considered to be at risk - and assigned to foster care institutions, we understand that one should think of the experience of these children as a different and unusual way of experiencing childhood. The research was carried out at Casa da Criança, a shelter located in Imperatriz / MA where children from 0 to 9 years old remain while they wait to return to the family or be put up for adoption, according to a court decision. There, children experience childhood among institutions - shelter, school, church - and are subject to numerous rules, having little space to exercise their agency power, which is why we analyzed Casa da Criança from the perspective of Goffman's total institution category. (1961). Ethnography resulted from the fieldwork, the ethnographic method being considered ideal for working in this context of institutionalization, since this investigation aimed at the dense description of the experience with childhood by children in a sheltered situation, and the ethical-methodological path was very more complex and covered in light and attentive steps, because above all it is necessary to protect children from exposure or danger, since they are under the tutelage of the State. In this way, we seek to combine field data with theory to understand the particularities of childhood experienced within a host institution in the city of Imperatriz / MA, as well as to understand how the construction of individuality occurs in the midst of this collective environment and how child autonomy is exercised, for example, constituting research on and with children.